2015
DOI: 10.1039/c5ra19439c
|View full text |Cite
|
Sign up to set email alerts
|

Construction of 3,5-dinitrated 1,4-dihydropyridines modifiable at 1,4-positions by a reaction of β-formyl-β-nitroenamines with aldehydes

Abstract: A novel and efficient method for the synthesis of 4--substituted 3,5--dinitro--1,4--dihydropyridines by a reaction of β--formyl--β--nitroenamines with aldehydes was developed. The reaction of nitroenamines with aldehydes leading to 1,4--dihydropyridines and the self--condensation of nitroenamines leading to pyridinium salt intermediate proceed competitively. The obtained 3,4,5--trisubstituted--1,4--dihydropyridines readily transformed into the corresponding pyridines in high yields. Introduction1,4--Dihydropyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In 2015, a novel method for the synthesis of 3,5‐dinitro‐1,4‐dihydropyridines 76,77 from β‐formyl‐β‐nitroenamines 74 and aldehydes 75 has been disclosed (Scheme ) . The composition of the reaction mixture and the yield of reaction products 76 depend on the structure and amount of the initial aldehydes 75 .…”
Section: Synthesis Of 14‐dihydropyridinesmentioning
confidence: 99%
“…In 2015, a novel method for the synthesis of 3,5‐dinitro‐1,4‐dihydropyridines 76,77 from β‐formyl‐β‐nitroenamines 74 and aldehydes 75 has been disclosed (Scheme ) . The composition of the reaction mixture and the yield of reaction products 76 depend on the structure and amount of the initial aldehydes 75 .…”
Section: Synthesis Of 14‐dihydropyridinesmentioning
confidence: 99%
“…2015 年, 他们 [109] 基于丁炔酸二酯的合成主要与醛/醌类化合物、 丙二 腈和芳类化合物为底物, 合成含有 5-腈基和 6-胺基的不 对称结构 1,4-DHPs, 其原理基于丁炔酸二酯和胺形成烯 酮胺中间体, 与丙二腈和醛形成的不饱和中间体经过 Hantzsch 反应类似历程的 Hantzsch-like 反应. 2010 年, Sun 等 [111] 在乙醇中三乙胺催化该类型反应, 高产率地得 到目标化合物(Eq.…”
Section: 新型反应的合成途径unclassified
“…In our previous work, we have demonstrated that 1-propyl-3,5-dinitropyridinium salt 2a·OTs is formed in situ upon treatment of N -propyl-β-formyl-β-nitroenamine 1a (R = Pr) with p -toluenesulfonic acid (TsOH), and formation of the salt 2a·OTs is confirmed by trapping as 4-arylated 1,4-dihydropyridine derivatives 3 with electron-rich benzenes. 6 On the other hand, 3,5-dinitropyridine 4 was obtained when N-tert -butylenamine 1b (R = t -Bu) was subjected to the same reaction, which is because a stable tert -butyl cation is readily eliminated ( Scheme 1 ). The easy access to 3,5-dinitropyridine 4 facilitates the N -modification to afford versatile N -alkyl-3,5-dinitropyridinium salts 2.…”
Section: Introductionmentioning
confidence: 99%